IMPACT OF SHOOT PRUNING ON ROOT DISTRIBUTION PATTERN OF LITCHI (LITCHI CHINENSIS SONN.) - DAS, BIKASH (The Bioscan, 2013)
Investigations were carried out at ICAR RCER, Research Centre, Ranchi during 2008 to study the effect of shoot pruning on pattern of root distribution in Senior-adult bearing plants of litchi cv. Shahi growing under alfisols of eastern India. Root samples were collected from control plants and plants which are under treatment of annual shoot pruning at a length of 75 cm at the time of harvesting since 2005. Shoot pruning resulted in significant reduction in the total weight of roots than that of control. The reduction in the total root weight of pruned plants can be attributed to a significant reduction in the weight of Grade-4 roots (>5.0 mm diameter). Significantly higher rate of biomass accumulation in Grade-4 roots of control plants was recorded at soil depths 0-30 cm (20.43 g/3683cc as compared to 3.74 g/3683cc in case of pruned plant) and 60-90 cm (15.83 g/3683cc as compared to 4.12 g/3683cc in case of pruned plant). With respect to distribution of roots at different distances from the trunk, significantly higher weight of Grade-4 roots could only be recorded at a distance of 50 cm from the trunk (13.12 g/3683cc as compared to 3.99 g/3683cc in case of pruned plant). With respect to total content of carbohydrate in different grades of roots at different distances and depths of soil, significantly higher values were recorded in case of Grade-4 roots (1.67 g/3683cc as compared to 0.49 g/3683cc in case of pruned plant).